Development and validation of RP-HPLC method for the simultaneous estimation of sitagliptin phosphate and dapagliflozin in bulk and marketed formulations with forced degradation studies - A. Khatik, Mohini; D. Ghule, Santosh; vengurlekar, Sudha; Jain, Sachin Kumar (Journal of Neonatal Surgery, 2025)
Introduction: The present study focuses on the development and validation of novel RP-HPLC method for the simultaneous estimation of Sitagliptin phosphate and Dapagliflozin in bulk drugs and marketed formulations. Method validation was carried out in accordance with International Council for Harmonisation (ICH) guidelines, assessing critical parameters such as accuracy, linearity, precision, specificity, limit of detection (LOD), and limit of quantification (LOQ)[1,2]. Additionally, forced degradation studies were performed under acidic, alkaline, oxidative, photolytic, and thermal conditions to evaluate the stability-indicating capability of the developed methods. These validated analytical tools are expected to offer reliable and reproducible results for routine quality assurance, regulatory compliance, and stability testing of combination antidiabetic formulations.RP-HPLC methods for their estimation, along with assessing their stability through forced degradation studies. Materials and Methods: The RP-HPLC method utilized a reversed-phase C18 column with a mobile phase composition optimized to achieve sharp, well-resolved peaks. Validation of method was performed according to ICH Q2(R1) guidelines, assessing parameters such as linearity, precision, accuracy, limit of detection (LOD), limit of quantitation (LOQ), ruggedness, and robustness. Forced degradation studies were conducted under various stress conditions including acidic, alkaline, oxidative, photolytic, and thermal environments. Results: The RP-HPLC method showed distinct retention times of 5.473 minutes for Sitagliptin and 8.611 minutes for Dapagliflozin. Both methods demonstrated high accuracy and precision with acceptable %RSD values (<2%). LOD and LOQ values confirmed the sensitivity of the methods. Among all stress conditions, the maximum degradation was observed under alkaline conditions, indicating that both drugs are less stable in basic environments. Conclusion: The developed RP-HPLC method is simple, sensitive, and reliable for the simultaneous estimation of Sitagliptin Phosphate and Dapagliflozin in bulk and marketed formulations. Their successful validation and application to forced degradation studies underscore their suitability for routine quality control, formulation analysis, and stability testing in pharmaceutical industries